To Cover the Many Sins of Galamsey Mining - Conradie, Ernst M. (Missionalia: Southern African Journal of Missiology, 2018)
This contribution calls attention to the environmental impact of mining in general and of galamsey mining in Ghana in particular as a theme for theological (and not merely ethical or pastoral) reflection. This topic is approached by placing it in juxtaposition with Christian discourse on sin, understood as a form of social diagnostics. By recovering the category of sin, this contribution seeks uncover the many sins of galamsey mining in the hope that such a prophetic critique will expose any ideological or idolatrous “cover-ups” but will nevertheless be “covered” by the gospel of the forgiveness of sin (see James 5:19-20.
free